Impact of Cyber-attacks on EV Charging Coordination: The Case of Single Point of Failure - ZEHİR, MUSTAFA ALPARSLAN (My University, 2022)
Expanding adoption of electric vehicles (EVs) and broad deployment of charging stations push the limits of distribution grid infrastructure and increase the importance of effective charging coordination. Smart EV chargers with several functionalities and charging coordination solutions that can manage the charging sessions of hundreds of EVs are becoming common, with the increasing risk of triggering significant operational problems in case of cyberattacks. The information exchange between the charging coordinator, distribution network operator, and users is essential in the scheduling of a large number of charging sessions, relying on customer preferences, without violating operational grid constraints. Both the user mobile apps used for charging session reservations and DSO-charging coordinator interfaces are vulnerable to cyberattacks which may cause considerable technical and economic consequences. An important concern is the potential impacts of attacks when a single node or communication link is compromised. This study investigates the impacts of false data injection (FDI) and hijacking attacks on EV charging coordination in case of a single point of failure. Hijacking of one user\"s mobile app and FDI attack on the DSO-charging coordinator interface are investigated by simulating a 24-hour scenario with 12 chargers, 34 realistic charging sessions, and an EV charging coordination approach based on each session\"s tolerance to delays. The study highlighted considerable negative impacts that could be encountered in case of a single point of failure in EV charging coordination.
Keywords: cybersecurity; electric vehicle charging; energy management; false data injection; hijacking